Generation and characterization of a human induced pluripotent stem cell (iPSC) line from a patient with BAG3 P209L myofibrillar myopathy-6 - Kerstin Filippi; Isabelle Riße; Luke M. Judge; Bruce R. Conklin; Bernd K. Fleischmann; Michael Hesse (Stem Cell Research)
Bag3 is important for protein homeostasis in mechanically stressed muscle proteins as member of the chaperone-assisted selective autophagy (CASA) complex. Patients with BAG3 P209L myofibrillar myopathy-6 (MFM6) carry a point mutation (p.P209L; c.626C>T) in the BAG3 gene and display clinical features such as restrictive cardiomyopathy, skeletal muscle dystrophy and polyneuropathy. To obtain a representative MFM6-model, biopsies from a female BAG3 P209L-patient were used to generate a human induced pluripotent stem cell (iPSC) line. For quality control, germ layer differentiation and pluripotency analyses were conducted. This iPSC allows us to characterize the pathophysiology of MFM6 and develop innovative experimental therapeutic strategies.